2021
DOI: 10.1101/2021.09.14.460368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of the autism-associated gene SCN2A alters synaptic development and neuronal signaling in patient iPSC-glutamatergic neurons

Abstract: SCN2A is an autism spectrum disorder (ASD) risk gene and encodes a voltage-gated sodium channel. However, the impact of autism-associated SCN2A de novo variants on human neuron development is unknown. We studied SCN2A using isogenic SCN2A-/- induced pluripotent stem cells (iPSCs), and patient-derived iPSCs harboring a p.R607* or a C-terminal p.G1744* de novo truncating variant. We used Neurogenin2 to generate excitatory glutamatergic neurons and found that SCN2A+/p.R607* and SCN2A-/- neurons displayed a reduct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have reported similar hyperexcitable neurons that carry ASD-and epilepsy-related mutations for SCN2A (Sodium channel protein type 2 subunit alpha) (67,68). Both epilepsy and ASD are also reported in patients with PRICKLE2 mutations (26,27), while Prickle2 knockout mice display a lower threshold for seizures (26) and ASD-like behaviors (27).…”
Section: Prickle2 Function In Asd and Epilepsymentioning
confidence: 97%
“…Recent studies have reported similar hyperexcitable neurons that carry ASD-and epilepsy-related mutations for SCN2A (Sodium channel protein type 2 subunit alpha) (67,68). Both epilepsy and ASD are also reported in patients with PRICKLE2 mutations (26,27), while Prickle2 knockout mice display a lower threshold for seizures (26) and ASD-like behaviors (27).…”
Section: Prickle2 Function In Asd and Epilepsymentioning
confidence: 97%